Self‐care perception and behaviour in patients with heart failure: A qualitative and quantitative study - Natasa Sedlar; Mitja Lainscak; Jerneja Farkas (ESC Heart Failure, 2021)
Abstract Background and objective Self‐care strategies in heart failure (HF) are effective for disease management, yet adherence in many patients is inadequate. Reasons are presumably multifactorial but remain insufficiently investigated; thus, we aimed to analyse self‐care adherence and associated factors in outpatients with HF. Methods and results To measure self‐care levels and explore barriers and facilitators to self‐care adherence in patients with HF, quantitative study using the European Self‐Care Behaviour Scale (EHFScBS‐9) (n = 80; NYHA II–III, mean age 72 ± 10 years, 58% male) and qualitative study using semi‐structured interviews (n = 32; NYHA II–III, mean age 73 ± 11, 63% male) were conducted. We detected lowest adherence to regular exercise (39%) and contacts with healthcare provider in case of worsening symptoms (47%), whereas adherence was highest for regular medication taking (94%). Using the EHFScBS‐9 standardized cut‐off score ≤ 70, 51% of patients reported inadequate self‐care. Binary logistic regression analysis showed significant influence of education (OR = 0.314, 95% CI: 0.103–0.959) and perceived control (OR = 1.236, 95% CI: 1.043–1.465) on self‐care adequacy. According to the situation‐specific theory of HF self‐care, most commonly reported factors affecting the process of self‐care were knowledge about HF self‐care behaviours (84%), experience with healthcare professionals (84%), beliefs about their expertise (69%) and habits related to medication taking (72%). Among values, working responsibilities (53%) and maintenance of traditions (31%) appeared as the most prevalent socially based values affecting motivation for self‐care. Situational characteristics related to the person (self‐confidence, 53%; adaptive coping strategies, 88%), problem (burdensome breathing difficulties, 56%; co‐morbidities, 81%) and environment (practical support from family/caregivers, 59%; financial difficulties, 50%) were also commonly reported. Conclusions Various factors, including health‐related beliefs, habits and socially based values, need to be taken into account when planning self‐care interventions in patients with HF. A patient tailored approach should be based on adequate patient evaluation, taking into consideration the particular personal and social context.